STUDY LITERATUR PEMAHAMAN MAHASISWA TENTANG LOGIKA INFORMATIKA DALAM PEMROGRAMAN - I Wayan Yudik Pradnyana; I Wayan Ady Juliantara; I Made Agus Widiana Putra; Wayan Eka Ariawan; I Nyoman Ariana Guna; I Wayan Mula Sarjana (Jurnal Ilmiah Sains Sosial, Kewirausahaan dan Kebudayaan, 2025)
Understanding informatics logic is an important foundation in programming learning because it plays a role in shaping algorithmic and computational thinking patterns. However, various studies show that students often experience difficulties in understanding the concepts of propositional logic, inference, predicate logic, Boolean algebra, and their application in program control structures. This article aims to conduct a systematic literature review of related studies to obtain a comprehensive picture of the conceptual and practical challenges faced by students, as well as the learning strategies used to overcome them. The research method uses a Systematic Literature Review (SLR) approach by analyzing relevant and open access articles published between 2017 and 2025. The results of the study indicate a gap between mastery of logic theory and its application in program code. Key findings include misconceptions in propositional logic, difficulties in simplifying Boolean algebra, limited representation skills through flowcharts and pseudocode, weak computational thinking, and recurring errors such as off-by-one errors and variable misconceptions. This study emphasizes the importance of integrating logic teaching with programming, a practice-based approach, and the use of visual media and interactive technology to improve student understanding.